Resource Disputes in South Asia: Water Scarcity and the Potential for Interstate Conflict - Patz, Alison; Lang, Katharine; King, Justin; Hillmann, Patrick; Condon, Emma (My University, 2009)
This report explores the role of water shortages related to transboundary rivers in interstate disputes in South Asia. The report analyzes the history and status of disputes, looking at the relationships between India and neighboring Pakistan, Bangladesh, and Nepal. The core of the report analyzes supply and demand with projections based on the PODIUM model. Water likely will continue to be a major source of conflict, as shortages will occur in India, Bangladesh, and, especially, Pakistan.
For PA 860: Workshop in International Public Affairs